Stainless steels for evaporators and concentrators. (Designers' handbook series, 2020)
The purpose of this publication is to help process engineers, designers, specifiers and purchasing officials better understand, select, use, and care for the corrosion and high-temperature-resistant stainless steels that are finding wider application in evaporator service.